(untitled) (Symposium on Natural and Applied Sciences, 2026)
The present study evaluates long-term hydrobiological and hydrochemical dynamics of the Talimarjan Reservoir (Uzbekistan) based on 2019–2023 monitoring data. Seasonal variation in dissolved oxygen (DO), inorganic nitrogen (N), and water transparency was analyzed together with plankton and benthic community structure. Mean dissolved oxygen ranged from 7.5 mg/L in summer to 11.9 mg/L in winter. Inorganic nitrogen varied between 0.009–0.049 mg/L, with maximum values observed in summer.